2020
DOI: 10.1038/s41467-020-14459-x
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-promoted cobalt-catalyzed radical hydroamination of alkenes

Abstract: Highly regio-and enantioselective intermolecular hydroamination of alkenes is a challenging process potentially leading to valuable chiral amines. Hydroamination of alkenes via metalcatalyzed hydrogen atom transfer (HAT) with good regioselectivity and functional group tolerance has been reported, however, high enantioselectivity has not been achieved due to the lack of suitable ligands. Here we report a ligand-promoted cobalt-catalyzed Markovnikovtype selective radical hydroamination of alkenes with diazo comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 58 publications
0
47
1
1
Order By: Relevance
“…It should be noted that an intermolecular asymmetric Markovnikov hydroamination of alkenes from electronically unbiased alkenes and donor-acceptor diazo reagents (77-84% ee) could potentially proceed via a MHAT mechanism as well. 141 In this case, a newly developed N-imidazolinylphenyl 8-aminoquinoline ligand was used. A detailed exploration of the enantiodetermining step is not included in this report, although the presence of radicals was implicated by cyclopropyl ring opening.…”
Section: Asymmetric Mhat Reactionsmentioning
confidence: 99%
“…It should be noted that an intermolecular asymmetric Markovnikov hydroamination of alkenes from electronically unbiased alkenes and donor-acceptor diazo reagents (77-84% ee) could potentially proceed via a MHAT mechanism as well. 141 In this case, a newly developed N-imidazolinylphenyl 8-aminoquinoline ligand was used. A detailed exploration of the enantiodetermining step is not included in this report, although the presence of radicals was implicated by cyclopropyl ring opening.…”
Section: Asymmetric Mhat Reactionsmentioning
confidence: 99%
“…93:7) in good yields using the cobalt(III)-catalysed alkene hydroamination methodology via HAT. 157 The optimal asymmetric induction was provided by using 6 mol% of a chiral NNN-tridentate ligand, the Nimidazolinylphenyl 8-aminoquinoline (IPAQ) ligand.…”
Section: Scheme 61 Cobalt Catalysed Intramolecular Hydroaminationmentioning
confidence: 99%
“…The radical could either escape from the cage and thus be captured by radicalophiles [2] or recombine with metal to form the cage‐collapsed organometallics complex which would undergo transmetalation with other metals and thus introducing new functionalities [3] . Catalysts based on cobalt are among the most studied systems for these types of transformations and proved extremely versatile (Scheme 1a, I and II) [2a–l] . Recently, Shigehisa, [4] Pronin, [5] and Zhu [6] suggested that the radical or collapsed alkylcobalt(III) intermediate could be further transformed into a carbocation or alkylcobalt(IV) species via single electron oxidation process in the presence of N ‐fluorocollidinium salt or excited photocatalyst, and which can be captured by nucleophiles (Scheme 1a, III).…”
Section: Methodsmentioning
confidence: 99%